TRENDS IN AGRARIAN STRUCTURE’S EVOLUTION IN THE LIGHT OF AGRARIAN CENSUS FROM 1996 AND 2002 - Wawrzyniak, Bogdan (Acta Scientiarum Polonorum. Oeconomia, 2004)
The aim of the paper is to show changes in family-run farms’ agrarian structure, which appeared, between the two agrarian censuses. The accelerating indicator of the change was restructuring former state farms which land supplied private sector. The analysis of the agrarian changes was carried out in four groups: smallholdings, middle farms, large-area farms and state sector. The greatest dynamism of changes were characteristic for large-area farms which developed ex-state properties by buying them or leasing. Middle farms changed not very much. The position of state sector dropped from 5.0% to 3.8%.